Studi Evaluasi Harga Minyak Mentah DuniaTerhadap Perang Rusia Ukraina - Iqbal Ilman; Nugroho Marsiyanto; Eko Prastio (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2023)
This study aims to evaluate how the Russian-Uk rainian war affects world crude oil prices. This conflict plays a significant role in disrupting the production and supply of crude oil in the Black Sea region, which could affect the global supply of crude oil. The evaluation method used is an analysis of the latest literature and economic data. The results show that the Russia-Uk raine war had a significant impact on world crude oil prices, although other factors such as oversupply and reduced demand due to the COVID-19 pandemic also play an important role in determining crude oil prices. Therefore, it is necessary to carry out a holistic and continuous evaluation of the various factors that affect world crude oil prices, including regional or geopolitical conflicts. This study provides a better view of how the Russo-Uk rainian war affected world crude oil prices and provides suggestions for a more comprehensive evaluation in the future. Based on the results of this research, it is hoped that it can become information and input for lecturers, researchers, practitioners, and all interested parties at the Faculty of Engineering, Bhayangk ara University, Jak arta Raya.